Ultrastructure of the alveolar nrtwork and its relation to coating on veáel walls in rlms infected by Ophiostoma novo-ulmi and in other plants affected with similar wilt diseases - Ouellette, G.B.=700 1 Rioux, D.; Simard, M.; Chamberland, M.; Cherif, M.; Baayen, R.P.
(Es, En)
ilus., 27 ref.
Keywords: FUSARIUM OXYSPORUM; HONGOS; CELULAS; ENFERMEDADES VASCULARES; ESPAÑA